The Application of Public Data in Forensic Real Estate Valuations: Problems, Limitations, Opportunities - A. Yu. Butyrin; V. M. Kruglyakova; I. A. Shipilova (Теория и практика судебной экспертизы)
One of the problems with the practice of legal proceedings is the determination of the legal authority limits of a forensic expert when he forms an array of initial data, the structure and content of which would provide a full and comprehensive research of the issues put before him by the body (person) having appointed the examination. The possibility of the specifed initial data completeness ensuring is suggested and substantiated in the article, arguments arising from the provisions of the law concerning neutralization of the traditional criticism directions of the expert in this part during his interrogation in the course of judicial proceedings on his conclusion are adduced.